Cross cultural and racial comparisons of job satisfaction in a South African hospital setting: Some empirical findings - D. T. Beaty; B. de Vries (South African Journal of Business Management, 1987)
In this study the authors compare the job satisfaction levels of white and coloured nurses employed at job parity and under similar working conditions. Perceptions of both groups concerning evidence of 25 job characteristics were also obtained. The findings reveal that although coloured nurses identify more job characteristics than their white counterparts, they are not significantly satisfied on intrinsic, extrinsic and overall satisfaction measures. Implications for the advancement of coloured workers into job parity with whites are discussed. Moderating variables that might have influenced these results are also addressed.
Keywords: 650